Rare Case of Ventricular Standstill and High-Grade AV Block in Patient with Thyrotoxicosis - Aryaputra, Achmad Bima; Bagaswoto, Hendry Purnasidha (The Indonesian Heart Association, 2022)
Background Stokes-Adams Syndrome can be caused by high-grade AV Block, ventricular tachycardia, and one of the uncommon cause, ventricular standstill. Although thyrotoxicosis is commonly presented as tachycardia, it’s unusual for AV blocks to occur, especially a high-grade one. Case Illustration A 45-year-old female was admitted with fatigue, dizziness, and recurrent episodes of unconsciousness. She had a history of hyperthyroid, routinely managed with Propylthiouracil and Propranolol. Physical examination showed HR: 30 x/min, and other unremarkable systemic examinations. Initial ECG showed 3:1 AV Block. Patient was managed with Dopamin and moved to ICU for further observation. In the ICU, suddenly she had a Stokes-Adam episode presented as a seizure, her monitor showing P waves with an absence of ventricular activity lasting for few seconds. Due to the condition of ventricular standstill, a Temporary Pacemaker (TPM) was installed urgently, and so patient’s vital sign was stable with pacing rhythm. We found Free Thyroxine (T4) level of 46.85 pmol/l, TSH of 0.005 ulU/ml, and unremarkable echocardiographic findings. Considering these results, we suspect that the cause of the ventricular standstill was due to thyrotoxicosis. Propylthiouracil and dexamethasone were given to manage the disease. After 7 days of treatment, she was discharged with sinus rhythm on her ECG. Conclusion Ventricular standstill is frequently associated with conduction blockages, but it can sometimes occur without them. Ventricular standstill treatment often necessitates the use of temporary pacing wires or a pacemaker. In thyroid crises, high-degree AV-block is uncommon, but when the euthyroid condition is restored, clinical status and conduction problems can be reversible.This article has a related Erratum.